Can bilateral bronchospasm be a sign of unilateral phrenic nerve palsy after supraclavicular brachial plexus block? - Souvik Chaudhuri; M D Gopalkrishna; Cherish Paul; Ratul Kundu (Wolters Kluwer Medknow Publications, 2012)
Ultrasound-guided peripheral nerve blocks facilitate ambulatory anesthesia for upper limb surgeries. Unilateral phrenic nerve blockade is a common complication after interscalene brachial plexus block, rather than the supraclavicular block. We report a case of severe respiratory distress and bilateral bronchospasm following ultrasound-guided supraclavicular brachial plexus block. Patient did not have clinical features of pneumothorax or drug allergy and was managed with oxygen therapy and salbutamol nebulization. Chest X-ray revealed elevated right hemidiaphragm confirming unilateral phrenic nerve paresis.